1948
DOI: 10.1128/jb.55.5.739-752.1948
|View full text |Cite
|
Sign up to set email alerts
|

Grisein, an Antibiotic Produced by Certain Strains of Streptomyces griseus

Abstract: It has now been definitely established that the ability to produce streptomycin is limited to a certain few strains of Streptomyces griseus. Numerous other strains of this organism, either isolated from natural substrates or taken from culture collections, were found to be unable to produce streptomycin or any other antibiotic. A certain few strains, however, were found capable of forming other antibiotics (Waksman, Schatz, and Reynolds, 1946). One such strain produced in the culture medium an antibacterial su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

1948
1948
2017
2017

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 52 publications
(15 citation statements)
references
References 3 publications
1
14
0
Order By: Relevance
“…He reported that the aerial mycelium of the organism showed proliferations of fertile branches at moderately close intervals along the axial hyphae, but no spirals. This early description and the illustrations correspond well with the production of tufts in the aerial mycelium of S. griseus found in recent photomicrographs (Carvajal, 1946a, Reynolds andWaksman, 1948). The early description of S. griseus (Waksman, 1919) covers the cultural and biochemical properties of the organism, which as a rule characterize rather well both the streptomycin-producing and grisein-producing cultures, with only certain minor differences.…”
Section: Resultssupporting
confidence: 81%
“…He reported that the aerial mycelium of the organism showed proliferations of fertile branches at moderately close intervals along the axial hyphae, but no spirals. This early description and the illustrations correspond well with the production of tufts in the aerial mycelium of S. griseus found in recent photomicrographs (Carvajal, 1946a, Reynolds andWaksman, 1948). The early description of S. griseus (Waksman, 1919) covers the cultural and biochemical properties of the organism, which as a rule characterize rather well both the streptomycin-producing and grisein-producing cultures, with only certain minor differences.…”
Section: Resultssupporting
confidence: 81%
“…However, addition of a chelating ion-exchange resin reduced the mass to 992.3 Da, equivalent to the loss of an Fe 3+ ion. Searching once more for known compounds with this mass drew our attention to the sideromycin, albomycin (Reynolds and Waksman, 1948;Stapley and Ormond, 1957). The identity of the compound was confirmed by mass fragmentation (Figure 4) and the previously identified albomycin biosynthetic cluster (Zeng et al, 2012) was located within the genome of WAC5484.…”
Section: Dereplication Allows For the Enrichment Of Rare Antibacteriamentioning
confidence: 73%
“…Actinomycetes ing streptomycin. Some produce grisein (358), some produce other antibiotics, and some produce no antibiotics at all.…”
Section: Berculosismentioning
confidence: 99%